2012
DOI: 10.4038/cmj.v57i1.4197
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a herbal formulation on the incidence and severity of upper respiratory symptoms in healthy volunteers: an open-label, randomised controlled clinical trial

Abstract: Introduction Many traditional preparations with varying combinations of herbs have been used for over 1500 years to treat upper respiratory ailments, and reduce their incidence and severity. Link Samahan ® is a formulation containing the extract of 14 such medicinal plants.Objectives To test the efficacy of Link Samahan ® in reducing the incidence and severity of upper respiratory symptoms in consenting healthy volunteers.Setting MAS Linea Aqua, a factory with over 3000 employees, having its own health care ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…These two ingredients are also constituents of the commercially available formulations called “Paspanguwa” along with three other plants parts, Zingiber officinale Roscoe., Oldenlandia corymbosa L., and Solanum surattense Burm.f.) and also in another commercial formulation called Samahan which is a combination of 14 ingredients including these two [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…These two ingredients are also constituents of the commercially available formulations called “Paspanguwa” along with three other plants parts, Zingiber officinale Roscoe., Oldenlandia corymbosa L., and Solanum surattense Burm.f.) and also in another commercial formulation called Samahan which is a combination of 14 ingredients including these two [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…LS has been previously shown to have protection against upper respiratory symptoms and hence it is currently widely used as a prophylactic agent [ 8 ]. Findings of the present study on rapid and enhanced gene expression of the co-stimulatory molecules leading to T-cell dependent B cell activation resulting in an effective IgG response supports the previous findings on the prophylactic effect of LS.…”
Section: Discussionmentioning
confidence: 99%
“…Its HPLC profile is provided as supplementary material . LS has been shown to have potent clinical effect in reducing the incidence, incidence over time and severity of fifteen upper respiratory symptoms [ 8 ]. Our previous studies have shown that LS possesses potent anti-inflammatory activity as shown by the significant reduction in in vivo anti-inflammatory activity (rat paw-edema model) and in inducing several cellular immune mechanisms contributing to anti-inflammatory activity such as inhibition of rat peritoneal phagocytic cell migration, production of reactive oxygen species (O 2 - assessed using quantitative nitroblue tetrazolium (NBT) assay) and reactive nitrogen species (NO 2 - assessed using Griess assay) and inducible nitric oxide synthase gene expression (assessed using reverse transcription polymerase chain reaction (RT-PCR) in rat peritoneal cells (unpublished data).…”
Section: Introductionmentioning
confidence: 99%
“…However, this formulation had not been registered as a herbal medicine by the Department of Ayurveda at the time of the RCT or its publication, as far as I have been able to ascertain. More recently two other RCTs, one with a genuinely herbal toothpaste [20], and another with a new formulation for colds and catarrh [21] have been published. The former significantly reduced salivary anaerobic bacterial counts, plaque index, and gingival bleeding in regular users, and the latter significantly reduced the incidence of 15 previously validated [22] and common upper respiratory symptoms, their incidence over time, and severity in healthy volunteers.…”
Section: Leading Articlementioning
confidence: 99%